The In Silico Characterization of Lycopene Forming Phytoene Desaturase (CrtI) Protein from Wheat Leaf Rust Fungi (Puccinia triticina) - Yehezkiel Vieri Polandos; Fenny Martha Dwivany; Karlia Meitha (3BIO: Journal of Biological Science, Technology and Management, 2023)
Carotenoid is a highly economical compound with a variety of bioactivities. However, 98% of total carotenoid used is still being manufactured by chemical-based synthesis, reducing bioactivities and is not environmentally friendly, hence the use of biofortification approach is sought.Lycopene forming phytoene desaturase (CrtI) is one of the key enzymes with the potential to develop as bioparts in recombinant carotenoid biosynthesis. CrtI from Puccinia triticina and Blakeslea trispora are considered as promising candidates due to the high amount of carotenoid inthe fungi. This research aims to characterize CrtI enzyme from P. triticina and B. trispora and the interaction with substrate, i.e.,15 cis-phytoene. The results showed that CrtI from P. triticina protein has 2 unique motifs, determining the three-dimensional CrtI protein structure. According to docking analysis, CrtI enzyme from P. triticina is predicted to bind to the substrate more spontaneously as indicated by the lower energy of affinity (-8.3 kcal mol-1) and more residues interaction compared to CrtI from Blakeslea trispora. In conclusion, the CrtI protein from P. triticina is suggested as the candidate for further exploration to design expression in a recombinant system.